Endoscopic resection of juvenile nasopharyngeal angiofibroma with lateral extension without embolization - Halwani Chiraz, PhD; Ferchichi Sana, MD; Awini Ayda, MD; Stambouli Nejla, MD; Askri Haithem, MD; Yazid Yazibene, (Professor) (Radiology Case Reports, 2025)
Juvenile nasopharyngeal angiofibroma (JNA) is a benign yet highly vascular and locally aggressive tumor. Surgical excision remains the mainstay of treatment, though it carries multiple risks, particularly related to intraoperative bleeding and tumor extension into deep anatomical spaces. This case report describes a 17-year-old male presented with a congestive, budding nasopharyngeal mass. Imaging findings were suggestive of JNA, with lateral extension into the infratemporal fossa and sphenoid sinus. MRI revealed a vascular blush of early moderate intensity, with intense enhancement and persistence of signal-free punctuation. Endoscopic endonasal surgery was performed without preoperative embolization. Tumor resection was facilitated by bipolar forceps coagulation as exposure progressed. Postoperative endoscopy confirmed complete excision. Histopathological examination confirmed the diagnosis of JNA. The patient was discharged on the first postoperative day. Follow-up at 1 month, 3 months, and 1 year showed no recurrence, with good local healing. This case highlights the advancements in endoscopic endonasal surgery, enabling the complete resection of highly vascularized tumors in deep anatomical locations without the need for preoperative embolization. The findings reinforce the importance of technical developments in improving surgical outcomes.